A 24‐year prospective study of dietary α‐linolenic acid and lethal prostate cancer. Issue 11 (23rd January 2018) - Wu, Juan; Wilson, Kathryn M.; Stampfer, Meir J.; Willett, Walter C.; Giovannucci, Edward L.
Abstract : Several meta‐analyses have attempted to determine the relationships between intake of α‐linolenic acid (ALA) and prostate cancer, but results were inconclusive. 47, 885 men aged 40–75 years without prior cancer in the Health Professionals Follow‐Up Study were prospectively followed from 1986 to 2010. Intake of ALA was determined from validated food frequency questionnaires every 4 years. We used multivariate Cox proportional hazards models to estimate hazard ratios (HR) with 95% confidence intervals (CIs) for lethal prostate cancer (distant metastasis or prostate cancer death). 386 lethal prostate cancers were diagnosed in the pre‐PSA era (before February, 1994) and 403 cancers in the PSA era. Intake of ALA was associated with increased risk of lethal prostate cancer in the pre‐PSA era (comparing top to bottom quintile of intake, multivariate‐adjusted HR = 1.78; 95% CI = 1.22–2.06; p trend = 0.003), but not in the PSA era (HR = 0.81; 95% CI = 0.56–1.17; p trend = 0.53), and the difference in associations was statistically significant ( p for interaction = 0.02). Mayonnaise, a primary food source of ALA intake in our cohort, was likewise only significantly associated with lethal prostate cancer in the pre‐PSA era. Among many other fatty acids that are correlated with ALA due to shared food sources, none was associated with lethal prostate cancer in the pre‐PSA era. In conclusion, higher intake of ALA was associated with an increased risk of lethal prostate cancer in the pre‐PSA era, but not in the PSA era. Potential reasons for the differential associations warrant further investigation. Abstract : What's new? Alpha‐linolenic acid (ALA) is considered a beneficial omega‐3 fatty acid. However, earlier studies reported a positive link between dietary ALA intake and lethal prostate cancer. In this study, the authors found that this association has now disappeared. The change coincides with more widespread screening for elevated serum PSA. The results in the pre‐PSA era may have been due to factors such as higher red‐meat and trans‐fat consumption, while current PSA screening allows earlier diagnosis of cancers that would have been lethal pre‐PSA. Further studies are needed to determine actual causes of this discrepancy.